THE ROLE OF SCHOOL PRINCIPAL IN IMPROVING TEACHER'S PROFESSIONAL COMPETENCE IN THE ELEMENTARY SCHOOL - Raja Mista (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2020)
This research is motivated by the needs to increase teacher’s professional competence. This research was conducted at SDN 020 Serumpun Jaya. The subjects of this study were all teachers in SDN 020 Serumpun Jaya, totaling 9 teachers. The purpose of this study was to determine the role of the school principal in improving teacher competency in elementary schools. The data in this study were about teacher professional competence taken directly from the SDN 020 Serumpun Jaya teacher. The research instrument used was a questionnaire about professional competence. The results showed that the indicator of teacher professional competence, mastering the competency standards and basic competencies of subjects or areas of development got the score of 80.4 with good categories. The second indicator is developing learning materials that are taught creatively got 71.3 with fair category. The third indicator, developing professionalism in a sustainable manner by taking reflective actions, scored 77.7 with good category, and the fourth indicator, utilizing information and communication technology for communication and self-improvement, scored 61.8 with fair category. It can be concluded that the role of the school principal is able to improve the teacher’s professional competence of SDN 020 Serumpun Jaya.